Developmental control of telomere lengths and telomerase activity in plants - Riha, K; Fajkus, J; Siroky, J; Vyskot, B (The Plant cell, 1998)
Telomere lengths and telomerase activity were studied during the development of a model dioecious plant, Melandrium album (syn Silene latifolia). Telomeric DNA consisted of Arabidopsis-type TTTAGGG tandem repeats. The terminal positions of these repeats were confirmed by both Bal31 exonuclease degradation and in situ hybridization. Analysis of terminal restriction fragments in different tissues and ontogenetic stages showed that telomere lengths are stabilized precisely and do not change during plant growth and development. Telomerase activity tested by using a semiquantitative telomerase repeat amplification protocol correlated with cell proliferation in the tissues analyzed. Highest activity was found in germinating seedlings and root tips, whereas we observed a 100-fold decrease in telomerase activity in leaves and no activity in quiescent seeds. Telomerase also was found in mature pollen grains. Telomerase activity in tissues containing dividing cells and telomere length stability during development suggest their precise control during plant ontogenesis; however, the telomere length regulation mechanism could be unbalanced during in vitro dedifferentiation.
Keywords: Plants; sekvence nukleotidů; telomerasa; tandemové repetitivní sekvence; Arabidopsis; hybridizace in situ fluorescenční; Plant Development; Models, Genetic; rostliny; DNA rostlinná; DNA, Plant; Telomerase; Tandem Repeat Sequences; telomery; modely genetické; In Situ Hybridization, Fluorescence; Base Sequence; vývoj rostlin; Telomere